The Effect of Financial Performance on Financial Report Disclosure in Manufacturing Companies Listed on the IDX - Khoirotullatifah, Nur laila; Nahar, Aida (Jurnal Rekognisi Akuntansi, 2024)
This research aims to determine the positive influence of liquidity on the disclosure of financial reports of manufacturing companies in Indonesia, to determine the positive influence of solvency on the disclosure of financial statements of manufacturing companies in Indonesia and to determine the positive influence of profitability on the disclosure of financial reports of manufacturing companies in Indonesia.This research uses a quantitative type of research by taking a sample of 39 consumer goods industry manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2020 - 2022. The number of samples was taken using a sampling technique using a purposive sampling technique, namely a sampling technique. based on certain criteria. The Independent Variables of this research are Liquidity (X1), Solvency (X2), Profitability (X3) and Activity (X4) as well as Financial Report Disclosure as the Dependent Variable (Y).The results of this research show that the Liquidity and Activity variables have a positive and significant effect on Financial Report Disclosure, while the Solvency and Profitability variables have no effect on Financial Report Disclosure. Meanwhile, simultaneously the variables Liquidity, Solvency, Profitability and Activity have a positive and significant effect on Financial Statement Disclosure and have an influence of 30.4%, while the remaining 69.6% is explained by other variables outside this research model.